Drug-loaded PEG-PLGA nanoparticles for cancer treatment - Zhang, Dan; Liu, Lin; Wang, Jian; Zhang, Hong; Zhang, Zhuo; Xing, Gang; Wang, Xuan; Liu, Minghua (Frontiers in Pharmacology, 2022)
Nanoparticles based on single-component synthetic polymers, such as poly (lactic acid-co-glycolic acid) (PLGA), have been extensively studied for antitumor drug delivery and adjuvant therapy due to their ability to encapsulate and release drugs, as well as passively target tumors. Amphiphilic block co-polymers, such as polyethylene glycol (PEG)-PLGA, have also been used to prepare multifunctional nanodrug delivery systems with prolonged circulation time and greater bioavailability that can encapsulate a wider variety of drugs, including small molecules, gene-targeting drugs, traditional Chinese medicine (TCM) and multi-target enzyme inhibitors, enhancing their antitumor effect and safety. In addition, the surface of PEG-PLGA nanoparticles has been modified with various ligands to achieve active targeting and selective accumulation of antitumor drugs in tumor cells. Modification with two ligands has also been applied with good antitumor effects, while the use of imaging agents and pH-responsive or magnetic materials has paved the way for the application of such nanoparticles in clinical diagnosis. In this work, we provide an overview of the synthesis and application of PEG-PLGA nanoparticles in cancer treatment and we discuss the recent advances in ligand modification for active tumor targeting.